Intervention effect of physical exercise on social anxiety of left-behind children - Yi Hou; Guihong Wang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The purpose of this study is to determine the intervention effect of physical exercise on left-behind children's social anxiety. 600 kids from grades 3 to 9 who were left at home by their parents were surveyed by questionnaire at six rural primary and secondary schools in Liaoning province. There were 590 valid questionnaires gathered, with an effective rate of 98.3 per cent. The ages of the participants ranged from 9 to 15, with an average of (11.58 1.83) years. The study was conducted anonymously in a classroom setting. Physical activity scale scores were negatively correlated with social anxiety (P<0.01), while psychological capital was positively correlated with physical activity (P<0.01). Social anxiety was negatively correlated with psychological capital (P<0.01). Regression analysis revealed that psychological capital mediated the relationship between physical activity and social anxiety in rural left-behind children, with a mediating effect value of -0.049. (-0.254). The findings indicate that awareness of social support has a substantial regulatory influence on the connection between physical activity and social anxiety (P 0.05). On the one hand, physical exercise can directly reduce social anxiety in left-behind youngsters; on the other hand, it can indirectly reduce social anxiety by developing their psychological capital.